Ethnographie und Videographie pädagogischer Praktiken "Ein-Blicke" in Projekte der Schul- und Unterrichtsforschung in einer Kultur der Digitalität - Schiefner-Rohs, Mandy; Heymann, Carina; Neto Carvalho, Isabel (Verlag Julius Klinkhardt, 2023)
School and teaching can hardly be thought of without the interconnectedness with digital media. Beyond the question of modes of media use, field observations informed by practice theory help to grasp pedagogical practices (not only) of media action in situ and in actu. The anthology brings together contributions with precisely this theoretical and methodological approach. From media pedagogical, school pedagogical and sociological perspectives, ethnographic or videographic style is used to access school practices in a culture of digitality. Literally, ""glimpses"" are given into different projects and approaches to classroom research.